2017
DOI: 10.5603/cj.a2017.0026
|View full text |Cite
|
Sign up to set email alerts
|

Optimal aNtiplatelet pharmacotherapy guided by bedSIDE genetic or functional TESTing in elective PCI patients: A pilot study: ONSIDE TEST pilot

Abstract: Background: Dual antiplatelet therapy (DAPT) is recommended after elective percutaneous coronary intervention (PCI) in PFT (36.5 ± 47 PRU) arms as compared to the control arm (176 ± 67.8 PRU), p = 0.01 and p = 0.03, respectively. PMI appeared in 17 (37%) (Cardiol J 2017; 24, 3: 284-292)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…3 The number of patients who are resistant to clopidogrel may be up to 35% of the population, which depends on the method of testing and the borders of high residual platelet reactivity. 5 A genotypebased antiplatelet therapy, as observed in a number of observational and randomized trials, is capable of overcoming high residual platelet reactivity [6][7][8][9] and may lead towards a decrease in the number of adverse cardiovascular events. [8][9][10][11][12][13][14][15][16] These results are proven by the results of a metaanalysis of 9000 patients on clopidogrel: the carriership of low function allelic variants increases the risk of major adverse cardiovascular events (MACE) 1.5-fold and the risk of stent thrombosis 2.8-fold.…”
Section: Introductionmentioning
confidence: 99%
“…3 The number of patients who are resistant to clopidogrel may be up to 35% of the population, which depends on the method of testing and the borders of high residual platelet reactivity. 5 A genotypebased antiplatelet therapy, as observed in a number of observational and randomized trials, is capable of overcoming high residual platelet reactivity [6][7][8][9] and may lead towards a decrease in the number of adverse cardiovascular events. [8][9][10][11][12][13][14][15][16] These results are proven by the results of a metaanalysis of 9000 patients on clopidogrel: the carriership of low function allelic variants increases the risk of major adverse cardiovascular events (MACE) 1.5-fold and the risk of stent thrombosis 2.8-fold.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent RCT, both genotyping (CYP2C19) and PFT (VerifyNew p2Y12 assay) all resulted in an improved platelet inhibition [25].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Multiple prospective studies investigated the impact on platelet reactivity as a surrogate measure of clinical outcomes. [31][32][33][34] A recent pragmatic, randomized trial of CYP2C19 genotyping implementation demonstrated that return of genetic test results influenced antiplatelet therapy prescribing after PCI. 35 In addition, multiple nonrandomized 36,38 and randomized trials 39,41 have examined the impact of genotype-guided-antiplatelet therapy on clinical outcomes.…”
Section: Clinical Outcomes Of Genotype-guided Antiplatelet Therapy Afmentioning
confidence: 99%